Wheat blast: A review from a genetic and genomic perspective - Hossain, Md. Motaher (Frontiers in Microbiology, 2022)
The newly emerged wheat blast fungus Magnaporthe oryzae Triticum (MoT) is a severe threat to global wheat production. The fungus is a distinct, exceptionally diverse lineage of the M. oryzae, causing rice blast disease. Genome-based approaches employing MoT-specific markers are used to detect MoT field isolates. Sequencing the whole genome indicates the presence of core chromosome and mini-chromosome sequences that harbor effector genes and undergo divergent evolutionary routes. Significant genetic and pathotype diversity within the fungus population gives ample potential for evolutionary change. Identifying and refining genetic markers allows for tracking genomic regions with stable blast resistance. Introgression of quantitative and R gene resistance into popular cultivars is crucial to controlling disease in areas where the pathogen population is diverse and well established. Novel approaches such as CRISPR/Cas-9 genome editing could generate resistant varieties in wheat within a short time. This chapter provides an extensive summary of wheat blast fungus M. oryzae Triticum (MoT) and offers an essential resource for wheat blast research in the affected areas.